The linear ANRIL transcript P14AS regulates the NF-κB signaling to promote colon cancer progression - Wanru Ma; Junhua Hu (BMC, 2023)
Abstract Background The linear long non-coding RNA P14AS has previously been reported to be dysregulated in colon cancer, but the mechanistic role that P14AS plays in colon cancer progression has yet to be clarified. Accordingly, this study was developed to explore the regulatory functions of ANRIL linear transcript-P14AS in cancer. Methods The expression of P14AS, ANRIL, miR-23a-5p and their target genes were detected by quantitative real-time polymerase chain reaction (qRT-PCR) and western blot. Cell supernatants of IL6 and IL8 were measured by Enzyme linked immunosorbent (ELISA) assay. Dual-luciferase reporter assays, RNA immunoprecipitation, or pull-down assays were used to confirm the target association between miR-23a-5p and P14AS or UBE2D3. Cell proliferation and chemosensitivity of NF-κB inhibitor BAY 11-7085 were evaluated by cell counting kit 8 (CCK8). Results When P14AS was overexpressed in colon cancer cell lines, enhanced TNF-NF-κB signaling pathway activity was observed together with increases in IL6 and IL8 expression. The Pita, miRanda, and RNA hybrid databases revealed the ability of miR-23a-5p to interact with P14AS, while UBE2D3 was further identified as a miR-23a-5p target gene. The results of dual-luciferase reporter, RNA pull-down, and RNA immunoprecipitation experiments confirmed these direct interactions among P14AS/miR-23a-5p/UBE2D3. The degradation of IκBa mediated by UBE2D3 may contribute to enhanced NF-κB signaling in these cells. Moreover, the beneficial impact of P14AS on colon cancer cell growth was eliminated when cells were treated with miR-23a-5p inhibitors or UBE2D3 was silenced. As such, these findings strongly supported a role for the UBE2D3/IκBa/NF-κB signaling axis as a mediator of the ability of P14AS to promote colon cancer progression. Conclusions These data suggested a mechanism through which the linear ANRIL transcript P14AS can promote inflammation and colon cancer progression through the sequestration of miR-23a-5p and the modulation of NF-κB signaling activity, thus highlighting P14AS as a promising target for therapeutic intervention efforts.